A BIBLIOMETRIC ANALYSIS OF CARBON NANOTUBES SYNTHESIS RESEARCH USING VOSVIEWER - Arbiansyah Aldhafi; Asep Bayu Dani Nandiyanto (International Journal of Research and Applied Technology (INJURATECH), 2021)
Carbon nanotubes (CNTs) have been rigorously studied during the past decade due to their extraordinary physical, chemical, mechanical, electrical and optical properties. The purpose of this research is to conduct bibliometric analysis in carbon nanotubes synthesis by combining mapping analysis using VOSviewer software. Application reference manager used to obtain research data, namely Mendeley. The data obtained is the result of a search based on the keyword " Synthesis Method of Carbon Nanotubes ". From the search results, 247 relevant published articles were found in the range of 2018-2022. The results showed that the number of articles researching carbon nanotubes synthesis has been increasing since 2018 until 2021. However, there have been 8 articles that published in the early of 2022, this number could be increased by the time. Research that is being popularly studied by researchers until today is about review due to the COVID-19 pandemic situation that forced the researchers to decrease experiment activity and physical interations. This research is expected to help and become a reference for researchers in conducting and determining the research themes to be taken.